Occupational Health Hazard and Safety Practices among Solid Waste Handlers of Damak Municipality - Rai, Esha; Limbu, Diptika (Butwal Campus Journal, 2025)
Waste handlers play a significant role in solid waste management but remains highly exposed to work-related hazards. This study aimed to gain a comprehensive understanding of the occupational safety and health hazards faced by the solid waste handlers in Damak Municipality to identify gaps and inform strategies to enhance the occupational health and safety of waste handlers. To achieve the objectives, a structured, closed-end questionnaire was developed and administrated using a purposive sampling technique. Additionally, key informant interviews were conducted to gain better insight into the field-level problems. The study revealed that the workforce, predominantly male (56%) faces significant occupational risks due to the labor-intensive nature of waste collection. Despite full access to personal protection equipment (PPE), only 60% of total workers were reported using consistently. A high prevalence of health issues was observed, including musculoskeletal disorders (66.7%), cuts and injuries (58.3%), respiratory problems (41.7%) and other related health problems. These findings are further supported by the fact that 44% of total workers had not received pre-work training. Moreover, the absence of medical facility, health services and health insurance at the work place identified through survey further exacerbated the worker’s vulnerability. These findings underscore urgent need of refresher courses on occupational health and safety (OSH) guideline, enforcement OSH protocols and mandate PPE use through a strict mechanism during working hour and provision for medical facility and health services to protect the well-being of waste handlers and promote safer work environment.